Exploring the constraints of jute cultivation and analysis of market value: A case study in Bhugroil, Paba Upazilla, Rajshahi - Amin, Md. Samiul; Rana, Md. Sakib; Khan, Sadia Anjum; Rahman, Md. Hasibur; Imon, Imam Hossain; Chowdhury, Md. Jayed (Journal of Scientific Agriculture, 2024)
As one of Bangladesh’s main cash crops, jute was known by many as the golden fiber. It has an important role in the economy. However, the existing conditions of the producer and trader of this cash crop are facing various problems and future advancement and economic growth are at risk. The study was conducted at Bhugroil in Paba Upazila of Rajshahi district. The researchers used both primary and secondary sources for data collection. The whole field survey was conducted using the PRA method and for primary data collection, different PRA tools were used. They selected some people for focus group discussion and collected information from key informants. In the study area, the researchers found out that the main problems of jute cultivation were less market value of jute fibers, water scarcity and insufficient rotten place, high production cost, lack of technological knowledge, plastic overtaking jute market, lack of subsidies and training, closing jute industries, pest attack, etc. The market analysis revealed that the market faced problems such as market syndicate, market price fluctuation, high transport cost, plastic overtaking jute market, closing of jute industries, low-quality jute fiber, unskilled labor force, less variety of jute products, no local market incentives for jute products, lack of market information, exporting only raw fiber and few products, etc. Considering the current situation, the researchers identified a few solutions and provided some recommendations like creating a government purchase center, price-determining policy, using modern technology and machinery, providing training and knowledge, discouraging plastic, creating new jute mills, credit facilities, skilled labor, improved transportation, versatile jute products, etc. The mentioned solution and recommendation can solve the problem of jute farmers and trades in selected areas and can be applied in areas facing similar problems.